2009
DOI: 10.1088/1748-9326/4/2/024002
|View full text |Cite
|
Sign up to set email alerts
|

Risk aversion, time preference, and the social cost of carbon

Abstract: The Stern Review reported a social cost of carbon of over $300/tC, calling for ambitious climate policy. We here conduct a systematic sensitivity analysis of this result on two crucial parameters: the rate of pure time preference, and the rate of risk aversion. We show that the social cost of carbon lies anywhere in between 0 and $120 000/tC. However, if we restrict these two parameters to matching observed behaviour, an expected social cost of carbon of $60/tC results. If we correct this estimate for income d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 25 publications
2
79
1
1
Order By: Relevance
“…For lower pure rates of time preference, the social cost of carbon rises (Guo et al 2006). For higher rates of risk aversion, the social cost of carbon falls, because its effect on the discount rate dominates its effect on the certainty equivalent (Anthoff et al 2009b;Anthoff et al 2009c). Table 2 shows the regional results for ρ=1% and η=1.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For lower pure rates of time preference, the social cost of carbon rises (Guo et al 2006). For higher rates of risk aversion, the social cost of carbon falls, because its effect on the discount rate dominates its effect on the certainty equivalent (Anthoff et al 2009b;Anthoff et al 2009c). Table 2 shows the regional results for ρ=1% and η=1.5.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of changes in the rate of risk aversion is harder to interpret, because it affects the discount rate, the equity weights, and, of course, the certainty equivalent (Anthoff et al 2009b;Anthoff et al 2009c). As the rate of risk aversion increases, uncertainty becomes more important, the impacts on developing countries get a higher weight, and future counts for less.…”
Section: Variations With Welfarementioning
confidence: 99%
“…Yet while δ is important to the economics of climate change, so too are η and g. As Anthoff, Tol and Yohe (2008), and Stern (2007) demonstrate, the costs and benefits of mitigating climate change are very sensitive to the specific parameter choice for η. Unfortunately, the debate following the Stern Review has shown that there is little agreement on precisely what value η should take.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the outcome of numerical modelling of climate policy is very sensitive to this parameter (Anthoff, Tol and Yohe, 2008;Stern, 2007). η has often been set to unity (Fankhauser et al, 1997;Nordhaus and Boyer, 2000;Stern, 2007;Tol, 1997), which gives the particularly tractable case of equation (2) where utility is the natural logarithm of consumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation